DESIGN AND APPLICATION OF PROCUREMENT OF VEHICLE PARTS IN MPC PT POS SURABAYA - Tanujaya, Wisnu Ramadhani; Wulandari, Sri Hariani Eko; Santoso, Rudi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT POS Indonesia is a service company in serving post which has mail processing center (MPC) who is active in processing, distributing and sending the post to working area. In one month, the letters and goods which are processed to be distributed are about 30.000 ton. To fulfill the customers’ needs, MPC is operating 35 vehicles. Up till now, there are many vehicles got troubles. It creates a bad operational and sending deferment. It happens because the company is not able to plan the supply and needs of spare-parts.From those problems, MPC PT POS Surabaya needs supplying application which is able to give information about the needs of spare-parts changing in every vehicle. From the needs result, it can be the reference to supply the spare-parts based on reorder point method. The application is able to produce information about warning system of spare-parts changing, repair activity log reports, report of reorder point and report of spare-parts procurement planning which are able to be used as the reference in determining spare-parts supplying.